CRISPR-mediated technology for seed oil improvement in rapeseed: Challenges and future perspectives - Ali, Essa; Zhang, Kewei (Frontiers in Plant Science, 2023)
Rapeseed not only provide considerable amount of edible oil with high nutritional properties but can also be used as a raw material for biofuel production in many industries. It is therefore in high demand to bring genetic changes in order to fulfill the need of human and of industries. Though traditional breeding techniques such as hybridization and mutagenesis remained the top methods for long time to create improved varieties in oilseed rape. Clustered regularly interspaced short palindromic repeats (CRISPR) is becoming one of the most valuable gene editing technologies that allow precise genome engineering, and open new ways for research in plant functional genomics. Though CRISPR has been used in many other crops for genetic improvement it is expected to be an effective tool for genome editing and molecular design in oilseed rape for seed oil improvement. This mini review will discuss and summarize the past and ongoing research and development in rapeseed in terms of seed oil improvement and fatty acid composition using CRISPR technology. In addition, the factors that hinder the efficiency of this tool and how to eliminate those factors will be briefly summarized. The improvement of CRISPR technology for getting better results in oilseed rape will also be considered here. This minireview will open new windows for researchers in Brassica napus oil improvement research and genetic improvement using CRISPR technology.